Carbohydrate availability regulates virulence gene expression in Streptococcus suis. - M Laura Ferrando; Peter van Baarlen; Germano Orrù; Rosaria Piga; Roger S Bongers; Michiel Wels; Astrid De Greeff; Hilde E Smith; Jerry M Wells (PLoS ONE, 2014)
Streptococcus suis is a major bacterial pathogen of young pigs causing worldwide economic problems for the pig industry. S. suis is also an emerging pathogen of humans. Colonization of porcine oropharynx by S. suis is considered to be a high risk factor for invasive disease. In the oropharyngeal cavity, where glucose is rapidly absorbed but dietary α-glucans persist, there is a profound effect of carbohydrate availability on the expression of virulence genes. Nineteen predicted or confirmed S. suis virulence genes that promote adhesion to and invasion of epithelial cells were expressed at higher levels when S. suis was supplied with the α-glucan starch/pullulan compared to glucose as the single carbon source. Additionally the production of suilysin, a toxin that damages epithelial cells, was increased more than ten-fold when glucose levels were low and S. suis was growing on pullulan. Based on biochemical, bioinformatics and in vitro and in vivo gene expression studies, we developed a biological model that postulates the effect of carbon catabolite repression on expression of virulence genes in the mucosa, organs and blood. This research increases our understanding of S. suis virulence mechanisms and has important implications for the design of future control strategies including the development of anti-infective strategies by modulating animal feed composition.